DIGITAL MARKETING OF BANKING SERVICES: TRANSFORMATIONS IN THE PANDEMIC PERIOD - Vasyl’tsiv , N.M. (The actual problems of regional economy development, 2021)
The article substantiates the necessity of using digital marketing in banking activity. Banking services are studied in the pandemic period. The goal of the article is to present the scientific approaches to studying transformations in digital marketing of banking services in the pandemic period. Preparation of the current article involved applying a set of general scientific and special methods of research. In particular, inductive and deductive methods were used for collecting and processing of data concerning the number of operating banks; economic analysis and comparison were applied to compose the bank stability rating; graphic method and method of economic and mathematical modeling – for visual presentation and calculation of the expected indices of increase/decrease of the number of banks by the linear and polynomial functions; abstract and logical method – for theoretical generalization and conclusion making. The research confirms the reduction dynamics in the number of banks, both foreign and private in the period of 2017-2020. The similar tendency is expected in the next 3-4 years that is justified by the linear and polynomial functions, where the determination factor R2 is equal to 0.8325 by the linear function, and 0.8896 by the polynomial function that confirms the model reliability. It is substantiated that the highest position in the rating of banks' stability is occupied by Raiffeisen Bank, which remains the leader in the quality of service in the Ukrainian banking sector. The advantages of Raiffeisen Bank are a wide range of standard and innovative services (salary, private and pension payment cards, Internet banking, deposits, loans, etc.) and the presence of about 3 million customers. To improve the competitive positions at the market, banks should modify their services in the pandemic period. Therefore, it is necessary for the banks to use innovative technologies like virtual reality, Internet banking platform, introduction of “payment holidays” services, and use of technologies of virtual and augmented reality. It is substantiated that virtual technologies solve several problems, namely they act as marketing instruments, they solve the tasks of sale departments, they serve as communication and information channels.